Rheology of Prestressed Circularly Symmetric Discs - Białkiewicz, J. (Engineering Transactions, 1983)
The paper presents the solution of the problem of creep of an annular disc prestressed by a system of concentric cables. Assuming - the distribution - of cables to be uniform, the magnitudes of individual prestressing forces are determined. The problem of interaction of the cables is solved by the method of iterations.